Patient Experiences of Receiving the Therapeutic touch of Nurses in Chronic Illness Care: A Qualitative Study - Rezkiki, Fitrianola; Kartika, Imelda Rahmayunia; Febrina, Cory; Fatin, Nisa Nurliana (Universitas Muhammadiyah Surakarta, 2026)
Therapeutic touch is a form of non-verbal communication, but its delivery in clinical settings often does not align with patient needs. Understanding the perspectives is essential to optimise its use in nursing care. Explore the experiences of Indonesian patients with chronic illness in receiving the therapeutic touch during hospitalisation. A qualitative descriptive design was used. Eight patients with chronic disease were recruited through purposive sampling. Data were collected through in-depth audio recordings and analyzed thematically. Results: Four themes emerged: Nurses’ ways of providing touch – techniques, intention and manner of initiating touch; Effects of touch – emotional comfort, reduced anxiety and perceived support; Timing of touch – appropriate moments when touch is expected or meaningful; Cultural and belief influences – feelings of shame, religious considerations and personal boundaries. Most of the patients expressed positive perceptions of therapeutic touch and acknowledged its benefits for comfort and connection. However, some hesitated due to cultural norms, religious values, or limited prior experience. Patients emphasised their right to therapeutic touch when nurses provide care, especially when it conveys empathy and genuine care. Practice Implications: Nurses should strengthen their use of therapeutic touch as part of holistic care. Health professionals are encouraged to integrate therapeutic touch intentionally and sensitively during hospitalisation.